2009
DOI: 10.1007/s11200-009-0039-1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between altitude of meteorological stations and average monthly and annual precipitation

Abstract: The aim of this study was to prove that altitudinal variability of average monthly and annual precipitation is better summarised when the altitude observed within a radius of several kilometres around a meteorological station is taken into consideration, instead of the altitude of the station itself. The use of the variable Z', which combines the altitude of the closest mountain with its distance from the station, is compared against the use of altitude alone in simple linear and multiple quadratic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 33 publications
1
18
0
1
Order By: Relevance
“…Altitude, as a topographic factor influencing the recovery of an evergreen forest 30 years after a fire, is discussed in Broncano et al [18], who document that higher altitudes are more favorable for the recovery of more water-demanding vegetation types. Similar to the present study, altitude is positively related to precipitation changes [65], while altitude is negatively related to changes in air temperature [66]. This combination favors the recovery of pine woodlands as they are more water-demanding vegetation types compared to the scrublands and garrigues of Karpathos Island.…”
Section: Discussionsupporting
confidence: 83%
“…Altitude, as a topographic factor influencing the recovery of an evergreen forest 30 years after a fire, is discussed in Broncano et al [18], who document that higher altitudes are more favorable for the recovery of more water-demanding vegetation types. Similar to the present study, altitude is positively related to precipitation changes [65], while altitude is negatively related to changes in air temperature [66]. This combination favors the recovery of pine woodlands as they are more water-demanding vegetation types compared to the scrublands and garrigues of Karpathos Island.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies mainly focused on the relationship between the altitudes and precipitation itself in present and future across the globe (Giorgi et al, 1997;Kang et al, 1999;Brunsdon et al, 2001;Kim, 2001;Kim et al, 2002;Gouvas et al, 2009;Kotlarski et al, 2012), especially in the mountain regions. Generally, these studies found an increasing amount of precipitation with altitude up to the highest elevations of the mountain or an elevation below the top, above which precipitation amounts did not increase any more.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the elevation dependency of precipitation have focused on relatively small spatial scales (e.g., for Japan: Sasaki and Kurihara 2008; for the UK: Brunsdon et al 2001;for Switzerland: Sevruk 1997; for the Czech Republic: Sokol and Bližň ák 2009; for Greece: Gouvas et al 2009; for northern Thailand: Kuraji et al 2009; for the west coast of India: Suprit and Shankar 2008), as have previous studies on future changes in the elevation dependency of precipitation (e.g., for the Alpine region: Giorgi et al 1997; for the southern Korean Peninsula: Im and Ahn 2011). To date, no studies have focused on the elevation dependency of precipitation in the Asian monsoon region, including the Tibetan Plateau and surrounding mountainous regions.…”
Section: Introductionmentioning
confidence: 99%